A cash‐strapped creator's reward‐based crowdfunding strategies with spot sales. (6th September 2022) - Guo, Xiaolong; Gao, Qian; Li, Tao; Yu, Yugang
Abstract: Reward‐based crowdfunding with the all‐or‐nothing mechanism helps cash‐strapped creators raise funds from potential consumers to develop new products. However, this mechanism may hurt the creator in the long run because possible buying frenzies of strategic consumers will cannibalize the demand for spot sales if the project succeeds with overfunding. Through a two‐period model incorporating a crowdfunding period and a spot sales period, we find that strategic consumers' purchasing decisions depend on the probability that they will like the product in spot sales. Moreover, we show that crowdfunding cannot be used to finance when the setup cost that a creator needs to pay for the production is sufficiently high. In addition, for creators who can use crowdfunding to finance, contrary to the intuition that they should not take risks when the market uncertainty is high, we find the opposite results when we take the joint effect of the setup cost and market uncertainty into consideration. To be specific, when the market uncertainty is high and the setup cost is higher than a threshold, the creator can optimally choose the risky strategy. Furthermore, the creator may benefit from market uncertainty when a high setup cost is required to launch the product.